Squeezing the muscle: Compression clothing and muscle metabolism during recovery from high intensity exercise - Sperlich, B.; Born, D.-P.; Kaskinoro, K.; Kalliokoski, K. K.; Laaksonen, M. S. (PLOS ONE, 2013)
The purpose of this experiment was to investigate skeletal muscle blood flow and glucose uptake in m. biceps (BF) and m. quadriceps femoris (QF) 1) during recovery from high intensity cycle exercise, and 2) while wearing a compression short applying ~37 mmHg to the thigh muscles. Blood flow and glucose uptake were measured in the compressed and non-compressed leg of 6 healthy men by using positron emission tomography. At baseline blood flow in QF (P = 0.79) and BF (P = 0.90) did not differ between the compressed and the non-compressed leg. During recovery muscle blood flow was higher compared to baseline in both compressed (P<0.01) and non-compressed QF (P<0.001) but not in compressed (P = 0.41) and non-compressed BF (P = 0.05; effect size = 2.74). During recovery blood flow was lower in compressed QF (P<0.01) but not in BF (P = 0.26) compared to the non-compressed muscles. During baseline and recovery no differences in blood flow were detected between the superficial and deep parts of QF in both, compressed (baseline P = 0.79; recovery P = 0.68) and non-compressed leg (baseline P = 0.64; recovery P = 0.06). During recovery glucose uptake was higher in QF compared to BF in both conditions (P<0.01) with no difference between the compressed and non-compressed thigh. Glucose uptake was higher in the deep compared to the superficial parts of QF (compression leg P = 0.02). These results demonstrate that wearing compression shorts with ~37 mmHg of external pressure reduces blood flow both in the deep and superficial regions of muscle tissue during recovery from high intensity exercise but does not affect glucose uptake in BF and QF.